Reinventing Islamic Education Paradigms: A Case Study of IMTAK–IPTEK Integration in the Era of Artificial Intelligence - Ningsih, Arum Gati; Hai, Kemas Abdui; Sanusi, Anwar; Harianto, Neldi; Al-Rawafi, Abdulkhaleq (Indonesian Journal of Islamic Religious Education, 2025)
This study explores the integration of IMTAK (Faith and Piety) and IPTEK (Science and Technology) in Islamic higher education, focusing on how lecturers combine spiritual values and Technology to enhance learning outcomes. Using a qualitative case study approach, data were collected through semi-structured interviews, participatory observations, and document analysis involving three lecturers and their students. Findings indicate that the integration of IMTAK and IPTEK creates a holistic learning experience, in which students not only acquire academic knowledge but also internalize the principles of faith and piety through personal reflection, ethical decision-making, and respectful social interaction. The use of digital platforms and AI facilitates interactive learning, critical thinking, and responsible academic practice, ensuring that Technology supports rather than replaces reflection and ethical behavior. This integrative approach also enhances students' understanding, intrinsic motivation, and social responsibility, producing learners who are academically competent, character-driven, and spiritually grounded. The study highlights a contemporary paradigm in Islamic education, where mastery of knowledge and Technology aligns with the development of faith, piety, and student character.